Implementation of Team Games Tournament (TGT) Assisted by Puzzle to Increase Learning Activity of Islamic Religious Education and Character - Masitah Ablisrah; Romi Maimori; Demina; Susi Herawati (JEICI - Journal of Education and Islamic Contemporary Issue, 2025)
This research is motivated by the low student activity in Islamic Religious Education and Character learning at SMPN 1 Salimpaung, which is still dominated by conventional methods, so that students are less enthusiastic, passive, and have difficulty understanding the material. This study aims to determine the effect of implementing the Team Games Tournament (TGT) method assisted by Puzzle media on increasing student activity. This type of research is a quasi-experimental study with a posttest-only nonequivalent groups design. The study population was all 32 seventh-grade students of SMPN 1 Salimpaung who were sampled using a total sampling technique. Class VII.1 was designated as the control class and VII.2 as the experimental class. Data were collected through questionnaires and observation sheets, then analyzed using normality tests, homogeneity, and t-tests. The results showed that the average student activity in the experimental class was higher than in the control class, both from the questionnaire results (79 compared to 67) and observations (78 compared to 55). The t-test at a significance level of 0.05 yielded a significance value of 0.000 with t count = -7.627 < t table = -2.042, so H1 was accepted. Thus, it can be concluded that the application of the TGT method assisted by Puzzle media is effective in increasing student activity in Islamic Religious Education and Character learning, especially in the oral, writing, motor, mental, and emotional aspects.